2010
DOI: 10.3758/s13414-010-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

Font size modulates saccade-target selection in Chinese reading

Abstract: In alphabetic writing systems, saccade amplitude (a close correlate of reading speed) is independent of font size, presumably because an increase in the angular size of letters is compensated for by a decrease of visual acuity with eccentricity. We propose that this invariance may (also) be due to the presence of spaces between words, guiding the eyes across a large range of font sizes. Here, we test whether saccade amplitude is also invariant against manipulations of font size during reading Chinese, a charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 36 publications
6
22
2
Order By: Relevance
“…Compared to Yan et al (2010), the average saccade amplitude in the present study was shorter, and there were more refixations. These results are in agreement with Shu et al (2011), who reported that saccade amplitude decreased and number of fixations at word beginnings increased significantly when parafoveal word length information was difficult to obtain. Nevertheless, our results suggest that saccade-target selection is still based on words for Chinese children, even though to a smaller extent.…”
Section: Discussionsupporting
confidence: 93%
“…Compared to Yan et al (2010), the average saccade amplitude in the present study was shorter, and there were more refixations. These results are in agreement with Shu et al (2011), who reported that saccade amplitude decreased and number of fixations at word beginnings increased significantly when parafoveal word length information was difficult to obtain. Nevertheless, our results suggest that saccade-target selection is still based on words for Chinese children, even though to a smaller extent.…”
Section: Discussionsupporting
confidence: 93%
“…However, more recently, Yan, Kliegl, Richter, Nuthmann, and Shu (2010) reported some conflicting results relative to the initial studies. First, they found that the initial fixation on a word was more likely to fall on the characters at the beginning of a word, resulting in a PVL curve peaked at the beginning of a word when more than one fixation is made on a word (for similar results, see Shu, Zhou, Yan, & Kliegl, 2011). This pattern is consistent with findings from unspaced English reading (Rayner et al, 1998) and findings from Japanese reading (Kajii, Nazir, & Osaka, 2001).…”
Section: Introductionmentioning
confidence: 91%
“…Indeed, Shu et al. () discovered that saccade amplitude decreased with increasing font size in reading Chinese, a result which was not found in alphabetic writing systems. Eye‐movement models of reading Chinese may thus need to incorporate a more flexible saccade‐targeting system.…”
Section: Computer Simulation Of Reading Chinesementioning
confidence: 98%
“…When the launch site was far away from the next word, readers tended to fixate at the beginning of the word. In a subsequent study, Shu, Zhou, Yan, and Kliegl () discovered that there were also more fixations towards the beginning of the word when the font size was large, presumably because the information at the end of the word was not available for parafoveal processing. The authors interpreted their results as readers’ attempts to extract information about the word boundary in the parafovea, which would be more successful when the next word was completely located within the perceptual span of the reader (but see Li, Liu, & Rayner, , for an alternative explanation based on a combination of character‐based and word‐based processing).…”
Section: The Roles Of Characters and Words In Reading Chinesementioning
confidence: 99%